2022
DOI: 10.3390/ijerph192013649
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Treatment of Endodontic-Periodontal Lesions: A Systematic Scoping Review of Experimental Studies

Abstract: Background: In this review, we evaluated the clinical efficacy of interventions used for the treatment of endo-perio lesions (EPL). Methods: A systematic scoping review of clinical trials was developed. Results: Seven clinical trials were studied. In at least one study group of six of the seven evaluated trials, endodontic and periodontal treatments were performed simultaneously. All trials showed improvement in probing depth in the studied groups; nevertheless, the experimental groups of five studies demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Another systematic review by Oktawati et al ( 2020 ) found that every study exhibited an improvement in probing depths, although it is notable that all were case studies. A systematic review of clinical trials by Ardila and Vivares‐Builes (Ardila & Vivares‐Builes, 2022 ) found that five out of seven studies (71.4%) had an improvement in probing depths, which is similar to the combined success and survival rate of the current study. Other studies had improved outcomes, such as Oh et al ( 2019 ), who found a 5‐year survival rate of 92.31%, and Kim et al ( 2008 ), who found a success rate of 77.5% with a minimum 1‐year follow‐up.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Another systematic review by Oktawati et al ( 2020 ) found that every study exhibited an improvement in probing depths, although it is notable that all were case studies. A systematic review of clinical trials by Ardila and Vivares‐Builes (Ardila & Vivares‐Builes, 2022 ) found that five out of seven studies (71.4%) had an improvement in probing depths, which is similar to the combined success and survival rate of the current study. Other studies had improved outcomes, such as Oh et al ( 2019 ), who found a 5‐year survival rate of 92.31%, and Kim et al ( 2008 ), who found a success rate of 77.5% with a minimum 1‐year follow‐up.…”
Section: Discussionsupporting
confidence: 79%
“…A systematic review of treatment modalities by Schmidt et al ( 2014 ) found possible evidence that initial endodontic treatment results in superior outcomes. Another systemic review by Ardila and Vivares‐Builes (Ardila & Vivares‐Builes, 2022 ) found that most studies treated EPLs with simultaneous endodontic and periodontal treatment, with a majority resulting in a statistically significant improvement in probing depths. Recent studies have focused on modern treatment advancements such as guided bone regeneration and incorporating platelet‐rich fibrin, which have both exhibited success in periodontal healing and attachment gain (AlJasser et al, 2021 ; Makkad, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been controversial reports on the optimum sequence and timing of RCT and PT of combined EPLs [17]. Ardila and Builes suggested simultaneous RCT and PT of EPLs [18]. However, when the root canals are infected, some researchers suggest performing RCT before any PT, to eliminate the intracanal infection before any cementum is removed [12].…”
Section: Introductionmentioning
confidence: 99%
“…This disease is characterized by the destruction of the supporting tissues of the tooth that can eventually cause tooth loss and results from a complex interplay between the subgingival biofilm and the host response [1]. Thus, host reactions regulate most of the tissue destruction that leads to the clinical expressions of the disease [2]. Plaque biofilm has a primary and gradual role in periodontal disease where mineralization into calculus turns as a holding device for non-calcified plaque, offering ideal settings for microorganisms to colonize and metabolize, thereby hindering periodontal therapy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, host reactions regulate most of the tissue destruction that leads to the clinical expressions of the disease [2]. Plaque biofilm has a primary and gradual role in periodontal disease where mineralization into calculus turns as a holding device for non-calcified plaque, offering ideal settings for microorganisms to colonize and metabolize, thereby hindering periodontal therapy [2,3]. Therefore, successful programs for the timely diagnosis and treatment of periodontitis may be pertinent to restricting the systemic damage that this disease can cause [2].…”
Section: Introductionmentioning
confidence: 99%